Mesenteric fibromatosis - Anant Pore; Sayali Pore; Ravi Bang; Sushantkumar Ikhar; Chetan Ronghe (Muller Journal of Medical Sciences and Research, 2023)
A 28-year-old patient reported having a lump in the right lower abdominal and pelvic area for the last 21 days, along with pain, anorexia, fever, and nausea. After a thorough investigation, an antero-posterior (AP) scanogram of the patient showed a clearly defined lump in this area. Histopathological examination showed mesenteric fibromatosis. Resection and anastomosis were done. Our case is one of the few known cases of the extremely rare condition fibromatosis of the mesentery. These tumors present a diagnostic and therapeutic difficulty due to their rarity. These tumors are still asymptomatic; however, they frequently appear as an asymptomatic mass. There are not any obvious therapy options. The preferred method of treatment is surgical excision with a wide margin; we underwent the same technique and the prognosis was good. Numerous single case reports with various and peculiar appearances and their difficulties exist. This case report aims to offer the current understanding of mesenteric fibromatosis as well as our clinical experience with the presented patient. Following surgery, the patient did well, and a 3-month follow-up revealed a typical recovery.